Features of the Organization of the Educational Process in the Conditions of Distance Learning - Oleksiuk , Olha; Teriaieva, Larisa; Teriaiev, Vitalii (Educological discourse, 2023)
Currently, among the many existing types and forms of education, distance learning is becoming one of the priority areas of pedagogical and educational-methodical activities of many universities, colleges, and general educational institutions. Therefore, the main existing traditional and modern types, methods and forms of education are analyzed in the article from the angle of suitability for use in remote form. Special attention is paid to the advantages, psychological and pedagogical features and problematic aspects of distance learning. The comparative characteristics of synchronous and asynchronous modes of distance learning were considered and carried out, the positive and negative aspects of each mode were determined. A general methodology for evaluating the effectiveness of methods, organizational forms, and types of training has been developed, which is based on theoretical and empirical methods of scientific research and makes it possible to objectively evaluate the effectiveness of training for a wide range of educational programs. To evaluate the effectiveness of methods and forms of distance learning, modern methods of scientific research were used. An analysis of teaching methods was carried out, namely methods for acquiring knowledge (motivational-learning, problem-searching, visual, game, reproductive) and methods for improving knowledge, skills and abilities (practical, interactive, creative, control and self-control methods). The results of the study showed that effective types of training are: distance learning, modular learning, interactive learning, dual education, problem-based learning and programmed learning. The most effective and relevant methods of distance learning have been determined: practical, problem-solving, visual, creative, interactive, motivational-learning methods and methods of control and self-control. According to the results of qualitative and quantitative analysis, the most effective forms of distance learning were identified, namely: individual, video conferences, Google applications, independent work, correspondence, free schedule, video training, game training, online chat. The results of the analysis enable teachers to make a qualified choice of the most effective methods and forms for both traditional and distance learning, and also indicate directions for improving the most effective approaches to learning. The intended prospects for further research consist in the improvement of the proposed approaches to increase the effectiveness of the forms and methods of training in order to raise the level of the quality of training.